"Wait, am I blogging?": an examination of school-sponsored online writing spaces - Hunt, Bud, author; O'Donnell-Allen, Cindy, advisor; Lucero, Rodrick, committee member; Reid, Louann, committee member (Colorado State University. Libraries, 2011)
In this study, I explore a school district's blogging engine, one that I helped to develop. Using both qualitative and quantitative methodology, I attempt to better understand how a school-sponsored online space might influence the type of writing occurring therein, while also trying to better understand how new tools like hyperlinks and commenting features on online text are changing student writing. I conclude that online writing looks a great deal like other classroom discourse, with teachers and students maintaining similar power and voice relationships in both spaces. More research is certainly needed, specifically around the role of these spaces in assessment and how feedback from teachers is incorporated by students into future work, but it seems that online writing spaces, at least in the school district studied, are quite similar to offline classroom composition spaces.
Wait, am I blogging?: an examination of school-sponsored online writing spaces
Keywords: writing; blogging; communication; education; learning; teaching